Peningkatan Kinerja Pertumbuhan Benih Ikan Gabus (Channa striata) dengan Probiotik EM4 - Jayadi, J; Harlina, H; Hamdillah, Andi; Nursyahran, N; Suryadi, S (Journal Galung Tropika, 2021)
The decreasing population of snakehead fish (Channa striata) in nature needs to be preserved through cultivation. The use of probiotics in cultivation can support increased production. This study aimed to determine the effect of the frequency of probiotics on survival, growth, feed conversion, and body proximate in snakehead fish fry for 60 days. The study was conducted using an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The treatment is the frequency of giving probiotics, including once a day, twice a day, three times a day, and without probiotics (control). The results showed that the frequency of probiotic administration affected survival, growth, feed conversion, and proximate content of snakehead fish seed bodies. The best frequency is the provision of probiotics twice a day.